Sān Ratthathammanūn kap kānphatthanā prachāthipatai nai rabop nitirat - Kunphon Phonlawan (Rūam botkhwām thāng wichākān (Thailand. Sān Ratthathammanūn), 2004)
Contributed articles on Sān Ratthathammanūn, a constitutional court of Thailand; volume brought its 6th anniversary.